National health problems and useful knowledge: lessons from public funding of diabetes research in Mexico. Issue 2 (3rd July 2019) - Natera, José Miguel; Rojas-Rajs, Soledad; Dutrénit, Gabriela; Vera-Cruz, Alexandre O.
ABSTRACT: Diabetes Mellitus has become an urgent national health problem in Mexico. We would expect knowledge production, particularly when is publicly funded, to be oriented towards the generation of useful applications and to collaborate in the solution of this disease. In this paper, we aim at analysing knowledge production for diabetes in terms of the Pasteur's quadrant, which consist of two axes: (i) 'consideration of knowledge use' and (ii) 'search for fundamental knowledge'. We organized 303 diabetes projects supported by CONACYT funds to operationalize a structural equation modelling (SEM) that frames diabetes research in Mexico. We found that most of research funds are not devoted to projects with high levels of 'consideration of knowledge use'; we believe that this is caused by the context of scientific funding in Mexico, which have incentives for basic research and does not count with sufficient mechanisms to orient the use of new scientific knowledge. We outline some policy recommendations. First, incentives should be focused on reorienting the research system towards a greater consideration of knowledge use. Second, the project approval process could also be modified to be more democratic, which the scientific community could discuss and find consensus with other social actors.